(untitled) (Research, Society and Development, 2020)
The objective of this work was the development of yogurt with jaboticaba jam added with fibers. This work was divided into three stages. The first objective was to make 5 types of jabuticaba jellies: standard (F01), with chia seeds 1% (F02) and 2% (F03) and with green banana biomass 1 (F04) and 2% (F05), all the jellies were subjected to microbiological and sensory analyzes. No difference was observed between the 5 samples when of the sensory analysis attributes were investigated. Subsequently, the formulations F01, F02 and F04 were characterized by centesimal analysis and were used in the preparation of "sundae" yogurt. F04 had a higher total soluble fiber and solids value and less moisture, and F01 had a higher concentration of reducing sugars. For yogurt, all the attributes evaluated in the sensory analysis acceptance test were shown to be within the acceptance scale (averages above 6.8). In the centesimal analysis, the F02 formulation differed from the other formulations with respect to the protein content (5.04 g / 100g) and fibers content (0.186 g / 100g). Regarding the count of viable lactic acid bacteria, a more detailed study should be carried out with the aim of increasing the addition of the initial culture to obtain an adequate final count. Also, both "ice cream" and yogurt can be vehicles for inserting fibers into food. The addition of chia seeds allowed an increase in the amount of fiber and protein in the developed yogurt.